2018
DOI: 10.1007/s00384-018-3101-z
|View full text |Cite
|
Sign up to set email alerts
|

Polypectomy versus surgery in early colon cancer: size and location of colon cancer affect long-term survival

Abstract: Polypectomy was as effective as surgical therapy for small tumors. For larger tumors, surgical therapy is better than polypectomy for right-sided tumors, but both are equally effective for left-sided tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 20 publications
3
14
0
Order By: Relevance
“…The rate of LNM has been previously reported to range from 7-15% [5][6][7][8], which is higher than our findings. Previously, it has been established that LNM may be highly correlated with lympho-vascular invasion [10][11], tumor size [12][13][14][15][16][17], TB [18] ,tumor invading in submucosa [19][20][21][22][23][24] and pathological differentiation [25][26][27]. In our study, lympho-vascular invasion was identified to be an independent risk factor for LNM in ECC.…”
Section: Discussionsupporting
confidence: 60%
“…The rate of LNM has been previously reported to range from 7-15% [5][6][7][8], which is higher than our findings. Previously, it has been established that LNM may be highly correlated with lympho-vascular invasion [10][11], tumor size [12][13][14][15][16][17], TB [18] ,tumor invading in submucosa [19][20][21][22][23][24] and pathological differentiation [25][26][27]. In our study, lympho-vascular invasion was identified to be an independent risk factor for LNM in ECC.…”
Section: Discussionsupporting
confidence: 60%
“…The rate of LNM has been previously reported to range from 7-15% [5][6][7][8], which is higher than our ndings. Previously, it has been established that LNM may be highly correlated with lympho-vascular invasion [10][11], tumor size [12][13][14][15][16][17], TB [18] ,tumor invading in submucosa [19][20][21][22][23][24] and pathological differentiation [25][26][27]. In our study, lymphovascular invasion was identi ed to be an independent risk factor for LNM in ECC.…”
Section: Discussionsupporting
confidence: 55%
“…A population-based study conducted in the U.S. reported no difference in the fiveyear survival rate between endoscopic resection and surgical treatment for mucosal or submucosal colorectal cancers (≤stage 1) with a longest diameter of ≤4 cm. 226 Mounzer et al also reported no difference in five-year colorectal cancer-specific recurrence-free survival rates (97.6% vs. 97.5%, p=0. 75) and colorectal cancer-specific mortalities (HR, 1.10; 95% CI, 0.72-1.69; p=0.65) between endoscopic resection and surgical treatment for colorectal cancer confined to the mucosa.…”
Section: Early Colorectal Cancermentioning
confidence: 93%